Isothermal Vapor-Liquid Equilibrium of Methanol + Glycerol and 1-Propanol + Glycerol - Annas Wiguno; Asalil Mustain; Wahyu Fazar Eka Irwansyah; Gede Wibawa (Indonesian Journal of Chemistry, 2016)
Isothermal vapor-liquid equilibrium (VLE) data for two binary mixtures of methanol + glycerol and 1-propanol + glycerol were determined at the temperature range from (313.15 to 363.15) K using a simple quasi-static ebulliometer. All systems showed that the vapor pressures increased with increasing alcohols (methanol or 1-propanol) concentrations at corresponding system. The Wilson, Non-Random Two-Liquid (NRTL) and Universal Quasi-Chemical (UNIQUAC) activity coefficient models were used to correlate the experimental data. Both systems showed slightly deviations from the ideal liquid phase behavior.